An Analysis Of Students Perception And Production Problems Of Pronouncing English Palato Alveolar Sounds - Sulistyorini, Dwi; Wibowo, Rachmat Ari (Universitas Ivet, 2021)
This study is about students’ error in perceiving and producing English palato alveolar sounds. The aims of this study are to describe how well the students perceive and produce English palato alveolar sounds and to find out the most common problems/errors encountered by the students whether in the level perception or production. This study used mix-method design. There were thirty eighth grade students as the sample of this study taken by convenience sampling technique. The data of this study were gained from two kinds of test, namely perception test in the form of listening test and production test in the form of speaking test. The results of both listening and speaking test were the source of data for this study. This study revealed that the eighth grade students were good in perceiving English palato alveolar sounds with errors 36% and were fair in producing English palato alveolar sounds with errors 53%. Therefore, it can be concluded that the most common problems faced by the students were at the production level and there were also some factors influenced them in producing English palato alveolar sounds, namely the non-existence of English palato alveolar sounds, the influence of orthographic writing, the influence of distractor sounds and the interference of mother tongue. It is suggested that the students practice a lot in pronouncing English palato alveolar sounds and the teachers provide many learning strategies and improve their teaching quality.